Coercive control and the criminal law - Wiener, Cassandra (Routledge, Taylor & Francis Group, 2023)
Introduction : assessing coercive control law reform -- The architecture and prevalence of coercive control -- Seeing what is 'invisible in plain sight' -- Domestic assaults and coercive control -- 'An unpleasant, closed-off world' -- Domestic stalking and the protection from Harassment Act 1997 -- From reluctant sex to rape -- Domestic sexual abuse and the Sexual Offences Act 2003 -- The Serious Crime Act 2015, s 76 -- Conclusion.